Unified method to prepare thermoplastic/thermoset soft polyurethanes reshape-able around room temperature on-demand - Chen, Hong Mei (2022)
We synthesized a range of polyurethanes (PUs) which can be either thermoset or thermoplastic, determined by the molar ratio of diisocyanate to diols (NCO/OH). These PUs are not only soft, but also can be reshaped around room temperature either permanently or temporarily. Although these PUs are produced in the same way, they have different thermomechanical properties, and can be thermoset or thermoplastic on-demand. We conceptually demonstrated the feasibility to apply this unified method not only in digital manufacturing of PU composites with gradient properties, but also in additive manufacturing (3D printing) in a way similar to fused deposition modeling (FDM). This unified method may be applicable to some other types of polymers as well.